Central ICT system SL2014: the way to reduce the transaction costs of European projects - Kępa, Marcin (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: European funds are these kinds of goods for which effective demand exceeds supply. The market value of European projects in Poland is estimated at approximately PLN 1125,44 bn, of which the EU co-financing is PLN 664,29 bn. Their effective use depends on the quality of the institutions responsible for their aggregation, allocation and proper expenditure (in accordance with the EU policies). Aim: The analysis of mechanisms determining the market game on the European project market in Poland in the light of the new institutional economics. Particular attention will be paid to the administrative tools that facilitate efficient long-distance communication between the parties to a project co-financing contract (central ICT system SL2014). Results: ICT systems constitute a part of a wider phenomenon commonly referred to as e-administration. It may be regarded as an institution in the meaning of the new institutional economics. This institution reduces the transaction costs related to handling European projects as well as the transaction costs in other areas connected with public governance. Wherever the e-administration can be applied (e-administration may be found useful in the case of public health emergencies that were triggered by the SARS-CoV-2 pandemic). Central ICT system SL2014 (as an element of e-administration) significantly reduced transaction costs in the field of handling European projects in the 2014–2020 financial perspective.